2013
DOI: 10.1016/j.molcel.2012.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Human TFAM in Mitochondria Impairs DNA Binding and Promotes Degradation by the AAA+ Lon Protease

Abstract: SUMMARY Human mitochondrial transcription factor A (TFAM) is a high-mobility group (HMG) protein at the nexus of mitochondrial DNA (mtDNA) replication, transcription and inheritance. Little is known about the mechanisms underlying its post-translational regulation. Here, we demonstrate that TFAM is phosphorylated within its HMG box 1 (HMG1) by cAMP-dependent protein kinase in mitochondria. HMG1 phosphorylation impairs the ability of TFAM to bind DNA and to activate transcription. We show that only DNA-free TFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
279
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(299 citation statements)
references
References 65 publications
16
279
1
3
Order By: Relevance
“…Several of the proteins that control mitochondrial DNA transcription have posttranslational modifications, including phosphorylation and acetylation. For example, TFAM is specifically phosphorylated (Lu et al 2013) and acetylated (Dinardo et al 2003), suggesting that its activity could be modified through cycles of acetylation/deacetylation in response to energetic signals. Another level of control of this mitochondrial transcriptional machinery is by inducing amounts of its components.…”
Section: Mitochondrial Transcriptionmentioning
confidence: 99%
“…Several of the proteins that control mitochondrial DNA transcription have posttranslational modifications, including phosphorylation and acetylation. For example, TFAM is specifically phosphorylated (Lu et al 2013) and acetylated (Dinardo et al 2003), suggesting that its activity could be modified through cycles of acetylation/deacetylation in response to energetic signals. Another level of control of this mitochondrial transcriptional machinery is by inducing amounts of its components.…”
Section: Mitochondrial Transcriptionmentioning
confidence: 99%
“…For a long time, the coordination of the two genomes (nuclear versus mitochondrial) was considered to be exclusively achieved by the nucleus-encoded proteins TFAM, TFB1M and TFB2M; among these, TFAM was believed to be essential for transcription, replication and maintenance of mitochondrial DNA (mtDNA) (Lu et al, 2013). Importantly, we have demonstrated that PGC-1a also resides in mitochondria and, at the mitochondrial matrix, associates with TFAM and with mtDNA, thereby coactivating the transcription of mtDNAencoded genes (Pagliei et al, 2013).…”
Section: Regulation Of Carbohydrate Metabolismmentioning
confidence: 99%
“…Upon import to mitochondria it performs multiple regulatory functions including mtDNA transcription, maintenance of mtDNA looping, coating and packaging (mitochondrial nucleoids) [59,69,70]. It contains facets for binding nuclear respiratory factor (NRF) 1 and NRF2 which act on the promoter of D-loop region leading to increased mtDNA copy number [71].…”
Section: Mitochondrial Transcription Factor a (Tfam)mentioning
confidence: 99%